Response by adults to increases in cigarette prices by sociodemographic characteristics. - Farrelly, Matthew C.; Bray, Jeremy W.; Woollery, Trevor (Southern Economic Journal, 2001)
Cigarette excise taxes are widely viewed by health economists as an effective tool to reduce cigarette consumption. However, those opposed to increasing cigarette excise taxes often state that the taxes unfairly target certain segments of the population, notably the poor and minorities. Some of this opposition may have been fueled by a lack of understanding of how the tax will affect the health and welfare of various demographic groups of interest. This article provides guidance to policy makers by estimating price elasticities among adults by gender, income, age, and race or ethnicity. Women, adults with income at or below the median income, young adults, African-Americans, and Hispanics are most responsive to cigarette price increases. For example, adults with income at or below the median are more than four times as price-responsive as those with income above the median. Reprinted by permission of the publisher.